Apparent evolutionary maladaptation and inference from reciprocal transplants - Fussmann, Gregor F.; Kopp, Michael (Frontiers in Ecology and Evolution, 2023)
In rapidly changing environments populations and species face a challenge to remain adapted and avoid extinction or replacement by fitter types. If evolutionary adaptation cannot keep pace with the speed of environmental change populations will exhibit varying degrees of maladaptation with respect to the current environmental state. Reciprocal transplant experiments are an established method for comparatively assessing the relative fitness of multiple populations in their respective environments. Here we use a quantitative-genetics model to show that inference from reciprocal transplants can be misleading when applied to populations that are in the process of adapting to environmental change. Specifically, we analyze (a) the case of two populations adapting to two different fitness optima starting from a suboptimal initial state and (b) the case of two populations attempting to adapt to changing trait targets that move at different speeds. We find that, in both scenarios, populations can undergo transitional fitness states that, if reciprocal transplant experiments were performed, would lead to the conclusion of (local) non-adaptation or maladaptation. This signature of apparent maladaptation occurs although both populations strictly follow an evolutionary trajectory dictated by the principle of fitness increase over time. Our results have implications for potential patterns of latitudinal replacement of populations/species with ongoing global change and might help shed light on the surprising finding (based on reciprocal transplants) that many populations in the wild fail to show a strong signature of adaptation to their local environments.